Comparative pharmacokinetics of the three echinocandins in ICU patients. (22nd July 2020) - Mainas, Efstratios; Apostolopoulou, Olympia; Siopi, Maria; Apostolidi, Styliani; Neroutsos, Efthymios; Mirfendereski, Helene; Marchand, Sandrine; Couet, William; Dokoumetzidis, Aris; Valsami, Georgia; Sambatakou, Helen; Dimopoulos, George; et al.
Abstract: Background: We conducted a prospective study in ICU patients of two tertiary hospitals in order to determine basic pharmacokinetic (PK) parameters, associated variation and target attainment rates for anidulafungin, micafungin and caspofungin. Methods: Serum samples from patients treated for 7 days with the standard doses of anidulafungin ( N = 13), micafungin ( N = 14) or caspofungin ( N = 7) were analysed by validated chromatographic methods. PK parameters determined with non-compartmental analysis were correlated with demographic, laboratory and disease severity characteristics. The percentages of patients attaining drug exposures described in the summary of product characteristics (SmPC) documents and preclinical PK/PD targets for stasis were estimated. Results: The median (range) AUC2 4 was 101.46 (54.95–274.15) mg·h/L for anidulafungin, 79.35 (28.00–149.30) mg·h/L for micafungin and 48.46 (19.44–103.69) mg·h/L for caspofungin. The interindividual variability of anidulafungin, micafungin and caspofungin AUC24 was 46%–58%, attributed mainly to variability in volume of distribution ( V), clearance (CL) and in both V and CL, respectively. Significant correlations were found between anidulafungin AUC24 and BMI ( r s = −0.670, P = 0.012) and liver enzymes ( r s = 0.572–0.665, P = 0.013–0.041) and between caspofungin C min and transaminase levels ( r s = −0.775 to −0.786, P = 0.036–0.041). Less than 50% of our patients attained the corresponding SmPC median AUC24 s and none of the patients attained the PK/PD targets for Candida albicans and Candida parapsilosis . Conclusions: Anidulafungin exposure in ICU patients was comparable with that reported in non-ICU patients and in healthy volunteers. Micafungin exposure was comparable to that of other patients but ∼30% lower than that in healthy volunteers, whereas caspofungin exposure was rather low (∼50% lower than in healthy volunteers). Larger interindividual variability (50%–60%) was recorded in ICU patients compared with other groups for all three echinocandins.